2018
DOI: 10.1108/ict-03-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Employee learning and development in virtual HRD: focusing on MOOCs in the workplace

Abstract: Purpose The purpose of this paper is to explore the potential of using massive open online courses (MOOCs) for employee learning and development in organizational settings by reviewing the literature and examining several cases from a virtual human resource development (HRD) perspective. Design/methodology/approach To collect information on MOOCs in the workplace, the authors reviewed peer- and non-peer-reviewed articles, book chapters, books, white papers, corporate websites and blogs, and business magazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Case findings by Park et al (2018) similarly support these notions; suggesting that, when deployed correctly, MOOCs can effectively enhance professional development and improve high-demand workforce skills and knowledge in a variety of contexts.…”
Section: Research Findings: What Do Managers Think?mentioning
confidence: 69%
“…Case findings by Park et al (2018) similarly support these notions; suggesting that, when deployed correctly, MOOCs can effectively enhance professional development and improve high-demand workforce skills and knowledge in a variety of contexts.…”
Section: Research Findings: What Do Managers Think?mentioning
confidence: 69%
“…Also, the use of massive open online courses (MOOCs) was explored for the purpose of employee learning and development and the researchers located 18 cases reporting that such courses offer promising opportunities for employees to engage in workplace learning (Park et al, 2018). Huang et al (2010) found that intrinsic and extrinsic motivating factors should be considered when designing virtual environments and offered the game-based adaptive performance platform for understanding and managing employee performance data vital for innovation.…”
Section: Opportunitiesmentioning
confidence: 99%
“…For example, Yoon and Lim (2010) stated that new technologies were driving swift changes in learning and performance and advocated VR skill development in HRD due to superior human memory retention when VR is compared with text materials or video training. Park et al (2018) advocated for assessing learners' skills with virtual tools and technologies along with required competencies for trainers. Rosenbusch (2020) recommended that HRD faculty be provided with essential tools and skills for redesigning customary courses and transform them into blended and online learning experiences.…”
Section: Opportunitiesmentioning
confidence: 99%
“…In contrast to academic MOOCs, when businesses integrate their MOOCs in curricula directly tied to an employee's ability to stay current in their field, earn a promotion, or do their work more effectively, motivation to use the MOOCs correlates higher for corporations (Egloffstein & Ifenthaler, 2017;Milligan & Littlejohn, 2014;Radford et al, 2014). Also, companies who have implemented MOOCs have seen employee satisfaction increase (Park, Jeong, & Ju, 2018).…”
Section: Moocs In Corporationsmentioning
confidence: 99%
“…with minimal effort and thus present lower cost and greater efficiency for corporate learning (Egloffstein & Ifenthaler, 2017;Park et al, 2018). Organizations can avoid the substantial cost of developing massive amounts of online content and more affordably utilize MOOC providers to curate and update content and design user-friendly interfaces (Egloffstein & Ifenthaler, 2017;Radford et al, 2014).…”
Section: Benefits Of Moocs In Corporations Moocs Can Be Maintained Amentioning
confidence: 99%